TEORI BELAJAR HUMANISTIK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Abd. Qodir (Nurul Jadid University, 2017)
This paper presents the theory of humanistic learning in improving student achievement. Learning is a process of acquiring science that is no other estuary to acquire values, knowledge, and practical skills as an effort to become a perfect human being. In this modern era education tends to be pragmatic. As a result of this is the process of education is no longer pay attention to student potential. The theory of humanistic learning is a theory whose focus of discourse focuses on the behavior of a human being. This theory assumes the student succeeds if the student understands her environment and herself. In this learning theory learners are expected to be free, courageous, unbound by others' opinions and manage their own personally responsibly without prejudice to the rights of others or violate applicable rules, norms, disciplines or ethics as well as teachers only as facilitators. With the free of students in developing their potential is expected to improve learning achievement.